Answer:
![-7^2 + 5^4](https://img.qammunity.org/2021/formulas/mathematics/high-school/h7e2l2qhx9feawsjipcsajt0fsd7obxpq7.png)
Explanation:
Essentially, you are seeing how much of each of the same term there is. Add the amount together, and it will be the exponent.
![(-7) * (-7) = -7^(1 + 1) = -7^2\\5 * 5 * 5 * 5 = 5^(1 + 1 + 1 + 1) = 5^4](https://img.qammunity.org/2021/formulas/mathematics/high-school/gkk96d7rhox9m8q9l19qtfxxwkz8anzjq2.png)
Combine the two terms together into an expression. Note that you cannot combine them.
is your answer.
~